Identifikasi Jamur pada Akar Tanaman Karet yang Berasal dari KP 2 (SEAT) Ungaran - Irfani, Hidayat; Himawan, Achmad; Kristalisasi, Elizabeth Nanik (AGROISTA : Jurnal Agroteknologi, 2025)
Fungi can grow and live in plant tissue. Endophytic fungi can provide benefits to plants in the form of increased resistance to disease attacks and can stimulate growth. This research aims to isolate and identify fungi in the roots of rubber plants in KP2 (SEAT) Ungaran. Sampling was taken at the KP2 (SEAT) Ungaran rubber plantation, followed by isolation and identification at the Laboratory of the Institute of Agriculture STIPER Yogyakarta. The research started from April to June 2024. Sampling used a diagonal method and the fungal identification method used a descriptive method. The results of isolation and identification obtained 13 isolates identified as the genus Colletotrichum sp. (B1P5U1 and B3P2U4), Fusarium sp. (B1P5U2, B1P5U3, B2P2U3 and B3P3U3), Geotrichum sp. (B2P5U1), Paecilomyces sp. (B3P1U5), Penicillium sp. (B1P1U3, B1P4U5, and B3P2U2), Rhizoctonia sp. (B2P4U3), Rhizopus sp. (B1P1U4), and 2 unknown isolates (B2P4U2 and B2P5U2).